2023
DOI: 10.1002/btm2.10588
|View full text |Cite
|
Sign up to set email alerts
|

Cancer vaccines in the clinic

Morgan E. Janes,
Alexander P. Gottlieb,
Kyung Soo Park
et al.

Abstract: Vaccines are an important tool in the rapidly evolving repertoire of immunotherapies in oncology. Although cancer vaccines have been investigated for over 30 years, very few have achieved meaningful clinical success. However, recent advances in areas such antigen identification, formulation development and manufacturing, combination therapy regimens, and indication and patient selection hold promise to reinvigorate the field. Here, we provide a timely update on the clinical status of cancer vaccines. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…The discovery of tumor antigens that could be targets of human T cells and antibodies ( 14, 15 ) stimulated ongoing research into cancer vaccines ( 16 ). Based on encouraging animal experiments, hundreds of phase I and II clinical trials were conducted, with some progressing to phase III; however, none showed good clinical efficacy and only one reached the approval stage ( 17 ). As was the case with many newer immunotherapies, it was determined that the immunosuppressive environment established in advanced cancer also compromised the success of therapeutic vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of tumor antigens that could be targets of human T cells and antibodies ( 14, 15 ) stimulated ongoing research into cancer vaccines ( 16 ). Based on encouraging animal experiments, hundreds of phase I and II clinical trials were conducted, with some progressing to phase III; however, none showed good clinical efficacy and only one reached the approval stage ( 17 ). As was the case with many newer immunotherapies, it was determined that the immunosuppressive environment established in advanced cancer also compromised the success of therapeutic vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Major histocompatibility complex class I (MHC-I) epitopes are predicted computationally, and these peptides are then synthesized and injected into a patient in a vaccine formulation. In several of the cancer vaccine trials, vaccination induced a detectable antigen-specific T cell response; however, very few have had meaningful clinical benefit . This could in part be due to the fact that peptide-based vaccines often suffer from weak immunogenicity, leading to poor effector T cell responses.…”
mentioning
confidence: 99%
“…In several of the cancer vaccine trials, vaccination induced a detectable antigen-specific T cell response; however, very few have had meaningful clinical benefit. 14 This could in part be due to the fact that peptide-based vaccines often suffer from weak immunogenicity, leading to poor effector T cell responses. The poor immunogenicity of peptide antigens can be attributed to several intertwined pharmacological barriers, including rapid clearance, poor uptake by dendritic cells (DCs), low accumulation in secondary lymphoid organs (i.e., lymph nodes), inefficient cross-presentation on MHC-I, and potentially, inappropriate choice of immunostimulatory adjuvant(s).…”
mentioning
confidence: 99%